2020
DOI: 10.5194/bg-2020-382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoupling salinity and carbonate chemistry: Low calcium ion concentration rather than salinity limits calcification in Baltic Sea mussels

Abstract: Abstract. The Baltic Sea has a salinity gradient decreasing from fully marine (> 25) in the West to below 7 in the Central Baltic Proper. Reef forming mytilid mussels exhibit decreasing growth when salinity

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 51 publications
0
17
1
Order By: Relevance
“…This could have led to an increase in the fraction of M. edulisdominated genotypes in the transition zone near AHP. AHP salinity monitoring data records indicate that salinity fluctuates strongly at this site and that salinity was relatively high in 2016 (Sanders et al, 2021).…”
Section: Salinity Dependent Local Adaptation and Differential Survival In Baltic Mytilus Larvaementioning
confidence: 88%
See 2 more Smart Citations
“…This could have led to an increase in the fraction of M. edulisdominated genotypes in the transition zone near AHP. AHP salinity monitoring data records indicate that salinity fluctuates strongly at this site and that salinity was relatively high in 2016 (Sanders et al, 2021).…”
Section: Salinity Dependent Local Adaptation and Differential Survival In Baltic Mytilus Larvaementioning
confidence: 88%
“…Adult Baltic Mytilus individuals were collected from three populations along the Baltic Sea coastline at the localities (KIE, average salinity 16 psu), Ahrenshoop (AHP, average salinity 11 psu), and (USE, average salinity 7 psu) (Figure 1 and Table 1) in spring 2016. Average salinities at each locality were analysed over a 2 to 3-year period and this information was used to calculate average salinity conditions for experimental procedures described below (Sanders et al, 2021). Considering the high levels of interspecific gene flow (see introduction), we will refer to Baltic mussels as "Western Baltic M. edulis" (KIE), "transition zone mussels" (AHP), and "Eastern Baltic M. trossulus" (USE) throughout the manuscript.…”
Section: Broodstock Sampling and Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…Calcium carbonate (CaCO 3 ) formation strongly depends on the seawater total alkalinity, availability of calcium ions (Ca 2+ ), and dissolved inorganic carbon (DIC), for example, carbonate ions (CO 3 2− ) and bicarbonate ions (HCO 3 − ). There is a salinity‐dependent trend that the concentrations of key carbonate species (e.g., CO 3 2− and HCO 3 − ) decrease proportionally with decreasing salinity (Beldowski et al, 2010; Müller et al, 2016; Sanders et al, 2021). Studying the skeletal variability along a salinity gradient is needful to reveal how calcifying organisms deal with a low CaCO 3 saturation state, that is, the ratio of the concentrations of Ca 2+ and CO 3 2− to the apparent solubility product of CaCO 3, which, in turn, depends on the temperature, pressure, and salinity.…”
Section: Introductionmentioning
confidence: 99%
“…is a worldwide, coastal, brackish, and estuarine mussel, that is very abundant in the Baltic Sea, acting as a foundation species and playing an important ecological role in benthic nutrient recycling (Kautsky & Wallentinus, 1980; Norling & Kautsky, 2008). Based on the example of the Baltic Mytilus spp., it was shown that the availability of seawater Ca 2+ and DIC for organisms affects calcification (Thomsen et al, 2018), yet the mechanisms underlying decreasing calcification rates along decreasing salinity are not fully understood (Sanders et al, 2021). In the Baltic Sea, alkalinity, the concentrations of Ca 2+ , the saturation state of CaCO 3 , and the ratio of calcification substrates (Ca 2+ and HCO 3− ) to the concentration of protons (H + ) decrease along the salinity gradient (Beldowski et al, 2010; Müller et al, 2016; Sanders et al, 2021) and create changing conditions for the calcification process, making the Baltic Sea an ideal model system to investigate the variability of skeletal mineralogy and geochemistry between calcareous invertebrates.…”
Section: Introductionmentioning
confidence: 99%